CV MASTERCLASS: AN INITIATIVE TO IMPROVE THE PROFESSIONALISM AND COMPETITIVENESS OF INDONESIAN WORKERS IN THE GERMAN LABOR MARKET - Sobara, Iwa; Indriwardhani, Sri Prameswari (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
The increasing demand for Indonesian workers with professional competence and high competitiveness in the international job market, particularly in Germany, requires individuals to be well-prepared in drafting application documents that meet global standards. Pratiwi & Mutmainah (2021) emphasize that career readiness is not only focused on individual aspects but also has a broader social impact by empowering communities to access better job opportunities. However, there remains a gap in understanding how to create an effective Curriculum Vitae (CV), especially in the context of German recruitment requirements, which demand a specific structure and format. In response to these challenges, the CV Masterclass workshop was designed to train participants in drafting and improving their CVs to make them more attractive, professional, and aligned with German standards. This activity aimed to help participants understand the key components of an effective CV, provide practical skills in writing and designing CVs, and boost their confidence in job applications. The methods used included direct training sessions, mentoring by two lecturers from the German Language Education undergraduate program at Universitas Negeri Malang (UM), and the distribution of questionnaires to measure the effectiveness of the activity. The workshop was held on May 20, 2024, at the Self Access Centre German Corner, Universitas Negeri Malang (UM), with 14 participants. The results showed that participants successfully created more competitive CVs relevant to the demands of the German job market. Additionally, they reported increased confidence in the job application process. This workshop also had a broader social impact by providing better access for Indonesian workers to secure jobs in the formal sector and participate in specialized programs in Germany, such as Ausbildung, Au-Pair, and professional employment in various fields. Through a follow-up mechanism, participants uploaded their CVs to Google Drive for review by facilitators, receiving valuable feedback to improve the quality of their CVs. The long-term impact of this activity not only enhances individual readiness to compete globally but also contributes to community empowerment. As more Indonesian workers possess high-quality CVs that meet international standards, their chances of securing employment in Germany increase significantly. Moreover, this training is expected to become part of a sustainable community service initiative, supporting broader economic and social growth.